THE EFFECT OF TOMATO JUICE (SOLANUM LYCOPERSIUM) AND PINEAPPLE JUICE (ANANAS COMOSUS L.) PROPORTIONS ON THE CHARACTERISTICS OF TOMATO JELLY CANDY - Rochman, Moch Fatchur; Azara, Rima (Antis-Publisher, 2025)
Objective: This study aims to determine the proportion of tomato juice with pineapple juice on the characteristics of tomato jelly candy. Method: This study used the Complete Randomized Block Design (CRBD) method with 1 factor (single factor) with a total of 5 treatments and repeated 4 times to obtain 20 experimental units. Results: The results showed that the difference in the proportion of tomato juice with pineapple juice had a significant effect on the water content of tomato jelly candy, but did not have a significant effect on texture, lightness, yellowness, and redness. Novelty: Tomatoes have their own taste (sweet, bitter, and smelly) so the addition of pineapple juice is needed to improve the taste, increase the economic value and diversify food products.